Tales from the Field: Teacher’s Habitus, Capital, and Agency in the Enactment of a Literacy Program - Fontejon-Bonior, Gina A. (Silliman Journal, 2022)
The success in the implementation of any educational innovation is influenced by teachers’ social dispositions and ability to navigate through the complexities of enacting the program in their local contexts. This assumption is informed by the practice theory as formulated by Bourdieu (1977, 1981) who emphasized the importance of one’s personal history in explaining human action. Bourdieu further posited that, while humans have the “ability to act upon and change the world,” one’s agency may be constrained by structures in a given social field. This study attempts to explore how teachers change their world and how they are transformed as they implement an Effective Literacy Instruction (ELI) in an island in Southern Philippines. Corollary to this, the study aims to explore the dynamic interplay between teachers’ habitus, their economic, social, and cultural capital and the structures that mediate the effective implementation of the ELI program. Data were collected through 30-to-40-minute telephone and personal interviews with eight participants, most of whom were in the training that I conducted as lead instructor of the program. The teachers’ narratives focused on their development as literacy educators as well as their successes and challenges in implementing the program. The narratives revealed that teachers’ dispositions are impacted by their personal histories and deeply ingrained social, cultural, and spiritual capital. Employing these, they position themselves in stances of power within the social field to ensure that the ELI program becomes a potent vehicle for the advancement of their advocacy for literacy education.